The impact of digital transformation in general education schools in facing challenges and continuous developments in the world from the point of view of teachers in Makkah Al-Mukarramah region - Alnemari, Maher Abdulrahman (Journal of Educational and Psychological Sciences, 2023)
The study aimed to reveal the impact of digital transformation on public education schools in facing continuous challenges and developments in the world from the point of view of teachers in Makkah Al-Mukarramah region. To achieve the objectives of the study, the descriptive analytical survey was used, through a questionnaire consisting of (30) items distributed in five domains, was applied to a random sample of (628) teachers from general education schools in Makkah Al-Mukarramah region. The results of the study showed that The impact of digital transformation on public education schools in facing challenges and ongoing developments in the world from the point of view of teachers in Makkah Al-Mukarramah region, with an overall average of (3.77 out of 5) with a grade of (high), and at the level of sub-fields; Teachers and students obtained the highest average (3.99), then teaching methods (3.82), third tests and evaluation (3.75), fourth technical skills (3.69), and fifth school curriculum (3.58), all with a (high) impact rating. The results also indicated that there are differences In teachers’ perspectives on the impact of digital transformation due to the educational qualification variable, in favor of "graduate studies", and there were no differences due to the practical experience variable. Based on these results, the researcher recommends presenting short and long-term plans by public education school administrations to implement digital transformation within the Kingdom’s Vision 2030, and holding training courses for teachers for developing teachers’ technical skills.